Актуальные вопросы микроморфологии животных - Мажуга, П.М. (Вестник зоологии, 1968)
The author presents a short review of the investigations carried out at the Department of cytology and histogenesis of the Institute of Zoology of the Ukrainian Academy, of Sciences with application of various modern methods of cytological analysis and concerning the structural, functional and metabolic indices of cellular differentiation. On the example of some derivatives of mesenchyme, the author also briefly considers the sources.. of definitive tissue systems and cell populations, the correlation of differentiation and physiological proliferation of cells, some mechanisms of forming ground substance and extracellular structure, intensity and type of biosynthesis in cells, found out in histogeneses of cartilaginous, bone, myeloid and some other tissues.